Perjanjian Tanah MENGKAJI KONSEP PERJANJIAN MENGENAI TANAH ATAU TEMPAT DARI PERMULAAN CIPTAAN DALAM KEJADIAN 1-2 DAN PEMULIHAN CIPTAAN DALAM WAHYU 21:1-2 - Andry Ligawan (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2023)
This article investigates the covenant of land or place in the creation account of Genesis 1-2 and the restoration of creation in Revelation 21:1-2 using lexical analysis. The development of the concept of land in each biblical period will be investigated with a focus on the aspect of relationship, place significance, and the notion of the kingdom. The article’s findings affirm the sameness in terms of meaning between the concept of land found in Genesis 1-2 and Revelation 21:1-2. In Genesis 1-2, the covenant of land between God and Adam regarding the providence of the land and the stewardship of Adam was meant to be a blessing for all the creations. Interestingly, Revelations 21:1-2 hints that the purpose was fulfilled in the person of Jesus.